Efficient Search Method to Solve the Fingerprint Identification Problem by Applying Machine Learning - Ruiz Rivera, María Elena (2022)
In biometrics technology, the fingerprint identification problem has been widely studied over the last decades due to its applicability in person identification cases. In casualty cases, recognition of the victim is required, which should be done unequivocally using fingerprint identification. The aim of this research is to innovate the fingerprint identification process, developing an efficient search method in a large database that allows finding a fingerprint in less time by classifying fingerprints into segments, according to their closest characteristics, using machine learning. Then, in a given segment, a discrete linear search algorithm is applied, with which the required fingerprint is located.